Financing the EU: New context, new responses - Clemens Fuest; Jean Pisani-Ferry (ifo Institute - Leibniz Institute for Economic Research at the University of Munich, 2020)
This paper discusses the introduction of new own resources to finance the EU budget. Currently roughly two thirds of the budget is financed from GNI-based own resources, which are essentially contributions made by the member states out of national tax revenues. While GNI resources are transparent, fair and in line with the principle of subsidiarity, they are criticised for leading to political debates that emphasise the cost of EU spending rather than on the benefits, and for contributing to the framing of discussions on the EU budget in terms of net balances, rather than value added through common policies and the provision of European public goods. Clemens Fuest and Jean Pisani-Ferry propose that the EU should receive a new source of funding in the form of revenue from the European emissions trading system (ETS). They recommend that revenue from the ETS be used to finance the EU fund for economic recovery (Next Generation EU), which was adopted in July.
Keywords: 330; EU-Haushalt; EU-Finanzbeziehungen; EU-Emissionshandel; EU-Staaten